Optimalisasi Sink Mark Index Pada Produk Plastik Dengan Variasi Ketebalan Ekstrim Menggunakan Simulasi Moldflow - Budiyantoro, Cahyo (Semesta Teknika, 2016)
Injection Molding Process is a closed cycle process involving 4 important factors that influencing product quality such as: process setting parameter, plastic material selection, product design and mold design. Ideally a plastic product is designed with uniform wall thickness since the thickness variation brought about negative effect on the final product. Those negative effects are warpage, sink mark or voids. Warpage is a bending failure of product, void cannot be observed as unfilled or holes on the cross section of the part, whereas sink mark is a deflected mark that can directly be seen on the surface of the part. Those 3 failures are normally caused by material accumulation and thermal rate differentiation. This research was a computerized based simulation using Autodesk MoldFlow Plastic Insight software to predict the 3 failures and to optimize the product quality by Sink Mark Index reduction, minimizing sink mark estimation and volumetric shrinkageÂ  due to extreem thickness variation. The selected specimen was a brush handle, a real product that can easily be found in the market. The errors of brush handle in fact was caused by poor design and the only way to improve its quality is from process parameters point of view. There are 5 possible factors in fixing the failures, each factor possessed 3 level of values, then according to the Taguchi approach of design experiment, there must be 27 experiments to be done. After having 27 times experiments with combination of level and factors, it can be summerized that by combining low melting temperature, high injection pressure and high holding pressure, a sink mark index of 2.642% and a volumetric shrinkage of 19.28% can be obtained, and those were the minimum values representing the best results of product. The extension of holding time did not give a significant influence on the target quality.